Design privacy of entering sequence in Qajarian houses and a framework for contemporary housing in Hot-Arid region of Iran / Faezeh Nabavi - Nabavi, Faezeh (2015)
Houses in the traditional architecture of Iran are all based on special principles. The goal of all of these buildings are to fulfill the requirement of the people and emphasizes the relationship between the buildings and the users. Traditional houses with courtyards, which are common in regions with hot-arid climates, demonstrate strict territoriality, and attempts to create private space for introversion. Such isolated lifestyles are not only the result of an attempt to conform to the climate, but are also a reflection of culture. The concepts of privacy have had a great impact on house culture and formation in Iranian Islamic architecture. The privacy measures that influence the design of the houses are representative of particular cultural norms. This research critically analyses design privacy of entering part in both traditional and contemporary houses in hot-arid region for establishing privacy framework for this part in contemporary houses. It includes four core objectives: to review issues of privacy in Iranian houses of Hot-Arid region (Traditional and Contemporary), establish the typology of entering spaces (entering sequence) related to the privacy in traditional houses of Hot-Arid region in Iran and analyse design privacy principles of these spaces, analyse the design principles that are related to achieving privacy at the entering spaces of contemporary houses in Hot-Arid region and the resident’s satisfaction on them and to establish a framework of design privacy in the entering spaces for contemporary houses (apartments). Sequential mixed method was used that includes both qualitative and quantitative approaches. Case study approach to analyse the design principles in entering sequence of traditional houses related to achieve privacy and establish the typology of this spaces. Quantitative approach to observe and measure plan layout of contemporary apartments, questionnaire survey to determine resident’s satisfaction and experts input to establish and validate suitable framework. Through eighty case studies, the typology of design privacy at the entering sequence in traditional houses identify. By completing this part, thirty of the case studies from the best samples in the most important city (Yazd) in the Hot-Arid region select. With these samples, researcher analyse the design privacy of the entering sequence in detail and categorize the entering sequence’ strategies that are related to achieve privacy. The results from this part help the researcher establish a framework of entering spaces for contemporary houses. Based on analysis, the lack of design privacy in entering space of contemporary houses caused problem for residents and the inhabitants of these houses. There are no arrangements in spaces in this part, and no hierarchy involved as well. Lack of these spaces led to a straight view of the inside of the house, which makes family members uncomfortable. This will allow guests to enter the houses without any inhabitants being able to welcome and receive them. By using these framework which matched by Iranian culture, religion and lifestyle it hopes contemporary houses be a better place for their residents. Based on the experts’ opinion, design principles of the entrance in achieving privacy for contemporary apartments should be added into architectural rules and instructions book for contemporary building.